Update on Predicting Severe Hyperbilirubinemia and Bilirubin Neurotoxicity Risks in Neonates - Chang, Pearl W.; Newman, Thomas B.; Maisels, M. J. (Current Pediatric Reviews, 2017)
Extreme hyperbilirubinemia and kernicterus, though rare, continue to occur despite the adoption of universal screening. Unless they are known to have glucose-6-phosphate dehydrogenase deficiency, infants who currently develop kernicterus in high resource countries are often otherwise healthy newborns discharged from the well-baby nursery. In this review, we highlight risk factors that increase the risk of a newborn ≥35 weeks gestational age developing severe hyperbilirubinemia, as well as the risk factors that increase the hyperbilirubinemic infant’s risk of kernicterus.
Keywords: neonates